An overview of fuzzy research with bibliometric indicators - Merigó, José M.; Gil-Lafuente, Anna M.; Yager, Ronald R. (Applied soft computing, 2015)
Number of annual publications in fuzzy research (articles+reviews) since 1965. •Bibliometrics in fuzzy research.•List of most cited papers on fuzzy topics of all time.•An overview of influential authors, institutions and countries.•Journal analysis in fuzzy research. Bibliometrics is a discipline that analyzes bibliographic material from a quantitative perspective. It is very useful for classifying information according to different variables, including journals, institutions and countries. This paper presents a general overview of research in the fuzzy sciences using bibliometric indicators. The main advantage is that these indicators provide a general picture, identifying some of the most influential research in this area. The analysis is divided into key sections focused on relevant journals, papers, authors, institutions and countries. Most of the results are in accordance with our common knowledge, although some unexpected results are also found. Note that the aim of this paper is to be informative, and these indicators identify most of the fundamental research in this field. However, some very influential issues may be omitted if they are not included in the Web of Science database, which is used for carrying out the bibliometric analysis.